La antropología primera de Nicea: espíritu, alma y cuerpo - Castellet i Sala, Jordi (Estudio agustiniano, 2025)
Saint Paul forged the triad of spirit, soul and body, in that order, in 1 Thess 5:23 when he wrote in his dismissal of the Thessalonians: "May the God of peace sanctify you completely, so that your whole spirit, soul and body may be kept blameless until the coming of our Lord Jesus Christ." This framework was largely shared and cultivated by Chruch Fathers such as Irenaeu (+200), Origen (+ 253), Ahanasius (+373) and Augustine (+430). At Nicaea, the humanity of God in Jesus Christ is emphasized, the Fahter and the Son Being of the same substance, homousious tou patrí. Athanasius confirm this in his statement that "God became human so that human beings might become God." We see the importance of affirming this complete humanity in Jesus Christ,which does not diminish his divininty, but rather enhances its power. Likewise, his humanity will be that which the human person hopes to achive, since he has been created in the image and likeness of the Word (Gen 1:26;2:7).